Mentorship Program Effectiveness in Early-Career Teacher Retention: Comprehensive Study - Jérôme J, Crassous,; Mirkov, Baćani; Franklin, Jaramillo (Global Synthesis in Education Journal, 2024)
The education sector has long struggled with the issue of early-career teacher attrition, with approximately 40-50% of new teachers leaving the profession within their first five months. This persistent challenge is attributed to various factors, including inadequate compensation, insufficient administrative support, and challenging workplace conditions. Despite the widespread implementation of mentorship programs, there remained significant gaps in understanding their long-term effectiveness and mechanisms of impact. This qualitative case study aimed to comprehensively examine the impact of mentorship programs on early-career teacher retention through a longitudinal analysis spanning five months. The research design incorporated multiple data collection methods, investigating 125 early-career teachers across urban, suburban, and rural contexts. The study sought to address critical research questions regarding mentorship's effect on retention rates, identification of most effective mentorship components, and variations across different demographic groups and school contexts. The findings revealed a compelling narrative of mentorship's transformative potential. While mentored and non-mentored teachers began with identical retention profiles, a significant divergence emerged over time. By the fifth month, mentored teachers demonstrated a 27.1 percentage point retention advantage, representing a 60.3% relative improvement in retention. Survival analysis showed mentored teachers had 2.85 times higher odds of remaining in the profession, with the most pronounced benefits observed in high-needs and rural school environments. The multivariate regression models confirmed mentorship's robust independent effect, even after controlling for various contextual factors. These results provide strong evidence that comprehensive mentorship programs represent a critical strategy for addressing teacher attrition challenges, offering actionable insights for educational policymakers and school administrators